Khrōngkān watthanatham Thai sāiyai chumchon Čhangwat Phrǣ : kānsongsœ̄m lān watthanatham (Samnakngān Watthanatham Čhangwat Phrǣ, 2009)
Promotion of cultural activities as a cultural project in Phrae Province, Northern Thailand.